A Flow Cytometric and Cytochemistric Analysis of Urine to Detect Early Urinary Tract Infection - Bargotya, Mona; Kumar, Lalit; Kachhap, Pinkey; Das, Payel; Sachdeva, Vidushi; Bhattar, Sonali (Annals of Pathology and Laboratory Medicine, 2020)
Introduction: Urinary tract infections (UTI) are infections affecting any part of the urinary tract and are most commonly caused by a multitude of bacteria. Most tests used these days to detect UTI are based on chemical test strips and cultures, both of which are labor and time-intensive. The aim of our study is to establish parameters that could detect UTI with high certainty. Material & Methods: The study was conducted in the Department of Pathology of Rajiv Gandhi Super Speciality Hospital, Delhi. The samples received between January to March 2017 were included in the study. All the samples were run in the Sysmex UX 2000, a fully automated urine analyzer. Results: A total of 236 patients were registered in this study. The study participants range from 4 years to 88 years with 56% males and 44% females. Out of these 21% were positive for UTI whereas 9% were inconclusive and 70% were negative. Cutoff values for white blood cells (WBC) and bacterial counts taken were 20.2 cells/Âµl and 143.2 cells/Âµl, respectively. Flowcytometric analysis of both WBC and bacterial cells showed high sensitivity (81%) as well as high negative predictive value (NPV) of 93%. Analysis of nitrites showed 97% specificity and 81% NPV, while leucocyte esterase showed 87% specificity and 92% NPV. Conclusion: Flow cytometry-based bacterial counts, total leucocyte counts, as well as nitrites and leucocyte esterase, could be used as screening tests for early as well as subclinical urinary tract infections and will reduce the need for urine culture.